Verb Conjugation in Different Languages: A Preliminary Study in Developing German Grammar Book Based Contrastive Analysis - Mantasiah R; Yusri Yusri; Arlian Fachrul Syaputra; Femmy Angreany; Hasmawati Hasmawati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
The purpose of this study was to investigate the verb conjugation process of German, Bahasa, and English. This study used a contrastive analysis which is one of approaches in applied linguistics. Data consisted of words and sentences in German, Bahasa, and English, and were analyzed descriptively. This article is a preliminary study which aims to do need analysis in developing German grammar book based contrastive analysis approach. Finding shows that there are 4 factors causing verb of a sentence should be conjugated: 1) Verb Conjugation Adjusted with Person as Subject,  2) Verb Conjugation Adjusted with active-passive voice sentence, 3) Verb Conjugation Adjusted with tenses of sentence, 4) Verb Conjugation Adjusted with quantifier factor of sentence subject.